Legal Protection For Land Rights Holders In The Implementation Of Electronic Certificates Under Regulation Of The Minister Of Agrarian Affairs And Spatial Planning/Head Of The National Land Agency No. 3 Of 2023 - Arif Rahman; Zuhrah; Syamsuddin (Lembaga Bale Literasi, 2025)
Advances in information technology have driven digital transformation in land administration through the implementation of electronic certificates as part of the modernization of Indonesia’s land registration system. This policy is legally grounded in Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities. This study aims to analyze the legal protection provisions for land rights holders in the implementation of electronic certificates, assess the effectiveness of their application within the land registration system, and identify the factors influencing legal protection for land rights holders. The study employs a normative legal research method using legislative, conceptual, philosophical, and case-based approaches. The legal materials consist of primary, secondary, and tertiary sources, analyzed using a descriptive-qualitative approach. The results indicate that, from a normative perspective, the implementation of electronic certificates has provided a sufficiently strong legal basis for ensuring legal certainty and legal protection for land rights holders. However, the effectiveness of their implementation is still influenced by the readiness of information technology infrastructure, the security of electronic systems, the quality of human resources, the integration of land data, and the level of public trust in digital systems. Therefore, strengthening regulations, enhancing institutional capacity, and improving information security systems are crucial factors in achieving optimal legal protection through an electronic land registration system.